Detection of Cucumber Mosaic Virus in Peanut ( Arachis hypogaea L.) in Argentina - de Breuil, Soledad (2005)
Peanut or groundnut (Arachis hypogaea L.) is an important oilseed crop in Argentina. Virus-like symptoms were observed in this crop during the 2000 growing season. Infected plants contained isometric particles c. 30 nm in diameter and tissue extracts reacted with a polyclonal antiserum to cucumber mosaic virus (CMV). A restriction profile typical of subgroup II was obtained for MspI cleavage of cDNA produced by using specific primers to CMV capsid protein (CP). These results were also confirmed by nucleotide sequence data on the CP gene. This is the first report of CMV subgroup II infecting peanut.